Marine Protected Areas in the High Seas: prospects and challenges in the context of international law - Gutiérrez Figueroa, Francisco (2017)
The paper reviews a topic of recent interest in the context of international law such as the designation of marine protected areas in the high seas. To that end, the author analyzes the importance of marine conservation in the global management of ocean resources, explores the recent developments related to the designation of marine protected areas in the high seas within the framework of the current international legal order and gives his views on the growing trend of establishing the aforesaid protected areas. Likewise, the paper briefly reviews the main international instruments and processes related to the conservation and sustainable use of marine biodiversity beyond areas of national jurisdiction.